Identification of a molecular marker linked to apomixis in Brachiaria humidicola (Poaceae) - Zorzatto, C.; Chiari, L.; de Araujo Bitencourt, G. [UNESP]; do Valle, C. B.; de Campos Leguizamon, G. O.; Schuster, I.; Pagliarini, M. S. (Wiley-Blackwell Publishing, Inc, 2010)
P>A bulked segregant analysis using RAPD technique was carried out to identify molecular markers linked to apomixis in a Brachiaria humidicola F(1) population that segregated 1 : 1 for the mode of reproduction (apomixis and sexual). A marker related to the apo-locus was found. Segregation data, together with this marker were used to generate a map of the region. This marker was located at 4.61 cM of the target locus, and it can be used in deploying marker-assisted selection for mode of reproduction in the hybrid progenies of this species.
Keywords: apospory; linkage map; RAPD; tropical forage grass